P-098 Epidemiology and Risk Factors of IgA Nephropathy in Patients with Inflammatory Bowel Disease. (February 2017) - Sharma, Prabin; Aguilar, Rodrigo; Chedid, Alice; Mordon, Armenia; Tabanor, Joy-Ann; Montero, Alex; Shammash, Jonathan; Asif Siddiqui, Omer; Li, Ping; Abi Nader, Mark
Abstract : Background: IgA nephropathy is the leading cause of nephritic syndrome and the most frequent kidney biopsy diagnosis in patients with Inflammatory Bowel disease (IBD) based on prior epidemiological studies. A possibility of a shared pathophysiology between IBD and IgA Nephropathy has been suspected. The aim of this study is to evaluate the risk factors, complications and predictors of in-hospital mortality of patients with Crohn's Disease (CD) and Ulcerative colitis (UC) who develop IgA nephropathy. Methods: Using the Nationwide Inpatient Sample Database, we identified patients between 2004 and 2012 with Inflammatory Bowel disease (ICD 9 Codes 555.0, 555.1, 555.2, 555.9, 556.0, 556.1, 556.3, 556.4, 556.5, 556.6, 556.8, 556.9) and IgA Nephropathy (ICD 9 Code 583.9). Patients with CD or UC who develop IgA nephropathy were compared to those without IgA disease. All categorical variables were compared with Pearson's χ 2 test and continuous variables were analysed with paired t test. Analyses were performed using SAS version 9.3 (SAS Institute). Results: Among the 268, 170 patients with CD and 152, 804 patients with UC admitted to the hospital between 2004 and 2012, we identified 127 (0.05%) and 80 (0.05%) cases of IgA nephropathy respectively. Patients with CD and IgA nephropathy, when compared to those without IgA disease have a significantly stronger association with male sex (52.0% versus 48.0%, P = 0.007), type 2 DM (2.4% versus 0.8%, P = 0.04), a positive HIV status (3.2% versus 0.2%, P < 0.001), Bronchiolitis Obliterans Organizing Pneumonia (0.8% versus 0.1%, P = 0.0006), Sjogren's syndrome (0.8% versus 0.2%, P = 0.05), sarcoidosis (2.0% versus 0.2%, P = 0.0015), acute diastolic heart failure (0.8% versus 0.1%, P = 0.01), hepatic encephalopathy (2.0% versus 0.3%, P = 0.003), renal osteodystrophy (2.4% versus 0.2%, P < 0.001), secondary hyperparathyroidism (2.4% versus 0.1%, P < 0.001), and coagulopathy (2.0% versus 0.4%, P = 0.02). Similarly, patients with UC and IgA nephropathy compared to UC without IgA are significantly associated with male sex (60.0% versus 40.0%, P = 0.01), primary sclerosing cholangitis (7.5% versus 2.0%, P = 0.0005), Sjogren's syndrome (2.5% versus 0.2%, P < 0.0001), optic neuritis (1.3% versus 0.02%, P < 0.0001) and acute systolic heart failure (1.35 versus 0.2%, P = 0.01). Acute tubular necrosis (5% versus 0.5%, P < 0.0001 and 7.5% versus 0.9%, P < 0.0001) and acute pouchitis (0.8% versus 0.1%, P = 0.009 and 3.8% versus 0.3%, P < 0.0001) is more common in both CD and UC patients affected with IgA nephropathy compared to those without IgA disease. Patients with IBD, either CD or UC who develop IgA disease do not have increased in-hospital mortality (1.6% versus 1.25%, P = 0.98) compared to those without IgA nephropathy. Conclusions: Male gender and certain rheumatologic diseases seem to predispose patients with CD or UC to develop IgA disease. Further studies are needed to unveil the link between these different disease processes. Overall, IgA nephropathy does not increase in-hospital mortality for patients with either CD or UC.